THE EFFECT OF HYDROLYSIS ON PROTEIN AND FAT LEVELS OF SNAKEHEAD FISH (Channa striata) - Finarti Finarti (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
Snakehead is freshwater fish with high protein. Snakehead fish also contains albumin which is the largest protein fraction in the blood, so its intake into the body needs to be maintained. To maintain the proteincontent in the snakehead body was to process it into soy sauce by hydrolysis method using bromealin enzyme media in pineapple. The research was conducted to determine the effect of hydrolysis time under12 hours on the chemical quality of snakehead fish sauce which was hydrolyzed using pineapple juice. The treatments used were hydrolysis time of 4, 6, 8 and 10 hours using a Completely Randomized Design (CRD) pattern with 3 replications. Testing of total protein, albumin protein and fat content using the UV vis spectrofotometry method. The results showed that the hydrolysis time did not affect the total protein, albumin protein and fat content of snakehead fish sauce. The test results showed that the hydrolysis time resulted in the highest total protein was 16.63%, albumin protein was 1.194% and fat was 0.47%. The hydrolysis time of 8 hours is the best hydrolysis time.